Primary and Specialty Outpatient Visits for Older Women With Urinary Incontinence: A Comparison of Nurses to the General Population. Issue 9 (7th September 2021) - Erekson, Elisabeth; Lane, Giulia; Mann, Jason; Austin, Andrea; Carmichael, Donald; Minassian, Vatche A.; Grodstein, Francine; Bynum, Julie P.W.
Abstract : Objective: We evaluated patterns of outpatient visits seen for urinary incontinence (UI) among women 65 years or older in the Nurses' Health Study and the general Medicare population. We were interested in understanding whether nurses, with high health literacy, may receive more care for UI than the general population. Methods: Medicare Fee for Service claims data for women aged 66–91 years were compared for Nurses' Health Study participants (n = 3, 213) and a propensity-matched sample from general Medicare Fee for Service beneficiaries (n = 3, 213) with 1 or more outpatient evaluation and management visits for UI in 2012. We examined the mean number of outpatient visits for UI and the type of provider seen, using t tests and χ 2 tests. Providers were categorized as specialist and nonspecialist providers using taxonomy codes. Results: The percentage of women 65 years or older who had an outpatient visits for UI over 12 months was 6.4% in the Nurses' Health Study cohort and 5.4% in the general population. The mean number of office visits for UI in 2012 was similar between nurses and the matched general population (mean = 1.8 vs 1.8; P = 0.3). A small percentage of women saw both nonspecialists and specialists for UI (9.3% in the Nurses' Health Study and 10.0% in the Center for Medicare Services cohorts). Conclusions: We found that less than 7% of older women had outpatient evaluation of UI symptoms during a 12-month period, despite UI being very common in this age group. This was similar in nurses and the general population, suggesting that even high health care literacy does not increase UI care seeking.